A mixed-methods study of Vietnamese university EFL students’ perception of native English-speaking teachers’ qualities - Tran, Bao-Chau Ngoc; Truong, Khoa Dang (Journal of Research on English and Language Learning (J-REaLL), 2024)
This study investigated Vietnamese university EFL students’ perception of the desired qualities of native English-speaking teachers (NESTs). A mixed-methods approach, including questionnaire data and semi-structured interviews, unveiled key attributes highly valued by the students. In order of importance, these encompassed engaging classroom interaction, robust subject matter knowledge, effective assessment strategies, and positive teacher-student relationships. Although these aspects of NEST qualities emerged as top priorities, the study also highlighted the comparative importance of other qualities in relation to classroom pedagogies, classroom management, personality traits, and professional behavior. In addition, the study identified ten highly endorsed qualities as strong predictors of an effective NEST model within the EFL context, as well as the rationale behind the students’ perception of these qualities. The study emphasizes the need for NESTs to consider and adapt their teaching practices to enhance EFL students’ learning experiences, while also providing implications for NEST preparation and training in Vietnam and in similar EFL contexts.